Симеизский склеп 1955 г. - Турова, Н.П. (Археологический альманах, 2012)
В фондах Ялтинского историко-литературного музея хранится археологический материал из раскопок раннесредневекового склепа, обследованного в 1955 году в Приморском парке поселка Симеиз. Симеизский склеп известен как один из раннесредневековых некрополей прибрежной части Южного Берега Крыма. Simeizskiy vault, investigational in 1955 L.A. Afanas’eva is chief. by the department of pre-revolution the pas of the Yalta city museum of study of a particular region, known as one of early medieval necropolises of off-shore part of South Bank of Crimea. Archaeological materials of burial vault, located in the Seashore park of settlement Simeiz never were fully published, the place of storage of report is unknown on excavations. Using a museum document, funds and scientific archive of the Yalta historical and literary museum an attempt to enter in a scientific turn all known us the archived and archaeological materials of one of early medieval burial grounds of South Bank of Crimea is first done.